The Appraisal Category of Judgement in Slovene Folk-Pop Music - Križan, Agata (Music with a Message: Words, Music and Propaganda 2, 2025)
Slovene folk-pop music is part of Slovene cultural heritage. This genre of music spread rapidly after WW2, mainly due to the brothers Avsenik, media and popularity of diatonic accordion among amateur musicians. The aim of this paper is to explore judgement, an appraisal category (Martin and White 2005), at a discourse-semantic level, in the lyrics of Slovene folk-pop music as a (potential) carrier of values, norms and stereotypes (i.e. ideology), which were (un)consciously and (un)intentionally promoted via radio and later TV broadcasting. Through the broadcasting of music, the mass media reach the audience with lyrics, also those with ideology (in)directly expressed.